Sanctions And Forms Of Responsibility For Investment Managers: Case Study on Mutual Funds PT. Falcon Asia - Akbar Rahkmat Irkhamulloh; Amelia Bellatrix Pantjo’u; I Putu Aris Udiana Putra; Samulel Rombe Tombe (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to examine the PT Falcon Asia Resources Management case which caused losses to investors. Also to find out Sanctions and forms of responsibility for Investment Managers to investors who suffer losses in mutual funds. The first method employs in this research was the statute approach or the statutory approach. The second method used was a conceptual approach. The data collection used in this article is secondary data collection by finding and collecting data that has already been published in books, newspapers, magazines, journals, online portals about mutual funds. The finding shows that on PT. Falcon Asia case, if the investor can prove that the Investment Manager has defaulted or acted against the law in accordance with the suit, then the Investment Manager is obliged to compensate for the losses suffered by the investor. The form of accountability of the Investment Manager is in the form of sanctions in accordance with the prevailing laws and regulations. Due to administrative sanctions, PT Falcon had its business license revoked by Bapepam. For criminal sanctions, it can be subjected to article 104 of the Capital Market Law with a penalty of 10 years and a fine of 15 billion. Meanwhile, in civil terms, PT Falcon's Investment Manager can be sued on the basis of Act Against the Law and default, so that if the sued is granted, the investor is entitled to give compensation. Keywords: Sanction, Form of Responsibility, Investor, Investment Managers,